A Systematic Review of The Effects of Decentralization on Health System Performance, Equity and Health Outcomes - Maneemai, Ongart; Maneemai, Kunwara; Rattanatanyapat, Pitchayut; Choorassamee, Jantima (Journal of Cultural Analysis and Social Change, 2026)
Decentralization has emerged as a central governance reform in health systems worldwide, motivated by the expectation that transferring authority and resources to subnational entities would enhance efficiency, responsiveness, and equity. Yet, three decades of empirical research reveal inconsistent evidence. This systematic review synthesizes global studies examining how political, administrative, and fiscal decentralization influence health system performance across five domains: access, efficiency, quality, equity, and population health outcomes. Following PRISMA 2020 guidelines, eight studies met the inclusion criteria from an initial pool of twenty-four records identified through major databases and organizational sources. The findings indicate that decentralization often improves access to maternal and child health services and immunization coverage when local autonomy is coupled with predictable fiscal transfers and adequate institutional capacity. However, evidence on efficiency and quality remains mixed, reflecting trade-offs between flexibility and coordination. Most critically, decentralization has not consistently reduced health inequities; in some cases, it has widened regional or socioeconomic disparities, particularly where redistributive mechanisms are weak. Contextual factors—such as fiscal capacity, governance quality, and political stability—emerge as decisive determinants shaping outcomes. Overall, decentralization should not be seen as a uniform solution but as a conditional governance reform whose success depends on institutional design, intergovernmental accountability, and equitable resource allocation.